2014
DOI: 10.15296/ijwhr.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-structural Study by Transmission Electron Microscopy: Effect of Omega-3 on Ovary Cell Organelles after Experimental Induced Poly Cystic Ovary Syndrome

Abstract: Objectives: Polycystic ovary syndrome (PCOS) is the most frequent cause of female infertility, affecting about 4% to 8% of women in the age of procreation. For evaluation the protective effects of omega-3 polyunsaturated fatty acid on ovarian structure in experimental PCO induced by estradiol-valerat, this research was done. Materials and Methods: Wistar female rats (n=40) were allocated into four groups, one control (n=10) and three test groups (n=30), that one group received omega-3 (60 mg/rat/orally/daily),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This could be due to the changes in the follicular fluid environment such as increased levels of androgens, triglycerides and insulin which may impact the oocyte volume ( 29 ). Our results also revealed that the mean thickness of zona pellucida significantly reduced in the PCOS group when compared to the control which is confirmed by the study conducted by Ouladsahebmadarek and Khaki who indicated a decrease in the thickness of zona pellucida and the distribution of microvilli in rats following estradiol valerate injection ( 30 ). Since oocyte and follicular cells are involved in the production of zona pellucid therefore the apoptosis of granulosa cells and follicular atresia could be the underlying cause for the reduction in ZP thickness ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…This could be due to the changes in the follicular fluid environment such as increased levels of androgens, triglycerides and insulin which may impact the oocyte volume ( 29 ). Our results also revealed that the mean thickness of zona pellucida significantly reduced in the PCOS group when compared to the control which is confirmed by the study conducted by Ouladsahebmadarek and Khaki who indicated a decrease in the thickness of zona pellucida and the distribution of microvilli in rats following estradiol valerate injection ( 30 ). Since oocyte and follicular cells are involved in the production of zona pellucid therefore the apoptosis of granulosa cells and follicular atresia could be the underlying cause for the reduction in ZP thickness ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, this work was set to investigate, for the first time up to the best of our knowledge, the reflection of cardiovascular risk factors associated with PCOS on the histopathological alterations in the cardiac muscle of adult female albino rats and whether broccoli extract can ameliorate these effects. In this work, we used a model in which PCOS was induced by a single intramuscular injection of estradiol valerate (EV) as employed by previous studies [29,34]. Estradiol valerate was reported to induce morphological changes in the ovaries like those of PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) was induced by a single intramuscular injection of estradiol valerate (EV) (16 mg/kg) [29] dissolved in 0.2 ml distilled water. During the experiment, the estrous cycle phases were monitored by the analysis of relative proportion of leukocytes, epithelial and cornified cells.…”
Section: Induction Of Pcosmentioning
confidence: 99%
“…According to the latest definition in 2003 (Rotterdam Criterion), PCOS has at least two criteria of three quantitative criteria, including the amount of menstrual bleeding (oligo menorrhea or amenorrhea), the clinical or biochemical symptoms of increased male hormones and sonographic findings suggesting polycystic ovary. Furthermore, fertility problems such as infertility, bleeding caused by dysfunction, endometrial carcinoma, and postmenopausal menopause are more common in patients with PCOS depression, low self-esteem, anxiety, and metabolic disorders such as obesity, impaired glucose tolerance, type 2 diabetes, lipid disorders, and hypertension suffer (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%